A Large Dental Hamartoma of Mandible in A Young Girl #x2013; Complex Odontoma#x201D; (Global Journal of Medical Research, 2018)
Odontomas are benign tumors of odontogenic tissue which are categorized as hamartomas because they result from developmental malformation of odontogenic tissues. They are classified into Compound Odontoma and Complex Odontoma. Compound odontomas are reported to be twice more common than complex odontomas. Complex odontoma is a rare tumor. Complex odontomas are usually asymptomatic, and they are accidentally noticed during a routine radiographic examination. But here we report and discuss a case of complex odontoma with unusually large size causing a disturbance in the eruption of second mandibular molar in a young girl who presented with chief complaint of pain and swelling on right side mandible.
Keywords: complex odontoma; hamartomas; mandible; odontogenic tumors